Molecular pathogenesis of thalassemia - Sunarto, Sunarto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1993)
Since the first description in 1925, thalassemia has been studied intensively and extensively. Thalassemia is inherited by Mendelian recessive genes, in which there is a mutation or deletion of the DNA nucleotide or results in defective production of one or more globin chains of the hemoglobin. There are two important forms of tha/assemias, a- and ft-thalassemia that are health problems in the tropical belt, extending from Africa and Meditenanian countries up to West Melanesia. The molecular studies of thalassemia and other hemoglobinopathies had discovered such a lot of abnormal hemoglobin structures and pathogenesis of the disease, so that the hemoglobin is now indeed a paradigm for our understanding of gene action at the molecular level. The thalassemia occurs essentially due to deletion, whereas 13thalassemia is mostly due to mutation of the gene(s). The understanding of the molecular pathogenesis of thalassemia is very essential for the diagnosis of the trait and especially for prenatal diagnosis, and in the future might be for genetic therapy.Key Words: thalassemia gene deletion gene mutation polymerise chain reaction haemoglobin